2011
DOI: 10.1073/pnas.1017669108
|View full text |Cite
|
Sign up to set email alerts
|

Structural model of the TRPP2/PKD1 C-terminal coiled-coil complex produced by a combined computational and experimental approach

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is caused by mutations in TRPP2 and PKD1, which form an ion channel/receptor complex containing three TRPP2 and one PKD1. A TRPP2 C-terminal coiled-coil trimer, critical for the assembly of this complex, associates with a single PKD1 C-terminal coiled-coil. Many ADPKD pathogenic mutations result in the abolishment of the TRPP2/PKD1 coiled-coil complex. To gain molecular and functional insights into this heterotetrameric complex, we computationally constructe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 47 publications
2
69
0
Order By: Relevance
“…From this screen of compounds predicted to modulate protein:protein interactions, Zinc01442821 (4-phenyl-1H-pyrrole-3-carboxylic acid, designated MS for molecular staple) was the best compound predicted to bind to the α regions of PC2, as shown in Figure 7A. Figure 7B) (17).…”
Section: Mechanical Stretch Regulates Oc or Ap2 Promoter Activities Bmentioning
confidence: 99%
See 3 more Smart Citations
“…From this screen of compounds predicted to modulate protein:protein interactions, Zinc01442821 (4-phenyl-1H-pyrrole-3-carboxylic acid, designated MS for molecular staple) was the best compound predicted to bind to the α regions of PC2, as shown in Figure 7A. Figure 7B) (17).…”
Section: Mechanical Stretch Regulates Oc or Ap2 Promoter Activities Bmentioning
confidence: 99%
“…We constructed a 3D model of the PC1:PC2 coiled-coil structure based on previous published structural information (17) and performed docking calculations (59, 60) to identify compounds …”
Section: Mechanical Stretch Regulates Oc or Ap2 Promoter Activities Bmentioning
confidence: 99%
See 2 more Smart Citations
“…These new heteromultimeric channels typically have many novel biophysical properties, modes of activation, or simply more efficient trafficking of the ion conducting subunit to the plasma membrane [42] . To date, the literature has shown that the TRPP2 subunit might assemble into both homomeric and heteromeric complex channels with polycystin-1 [43,44] , TRPC1 [29,[45][46][47] , TRPC3 [48] , TRPC4 [49] , TRPC5 [50] , TRPC7 [48] and TRPV4 [51][52][53] . The pharmacology associated with TRPP2 is poorly understood.…”
Section: Trpp2's Expression Pattern and Agonists And Antagonistsmentioning
confidence: 99%